Jom Baca@PHS: Building Foundation for Lifelong Learning - Mohd Napiah, Mohd Kamal; Ibrahim, Nor Azan; Ibrahim, Intan Haryati; Ahmad, Rosnani; Fesal, Fujica Azura; Azmi, Noor Adilah; Mahabat @ Mohamed, Muhammad Hanifah; Jamaluddin, Hazwani; Ramlee, Hazaralie; Mansor, Mohd Hezri; Azmi, Muhamad Amin; Abdul Halil, Mohd Hazlee (2014)
Universiti Sains Malaysia (USM) is a pioneering university that strives to empower future talent and next generation towards a sustainable knowledge transformation. Hamzah Sendut Library in supporting this effort has formed the Reading Campaign Committee with the tagline „Jombaca@PHS‟. This committee is established to promote love for books and reading culture to Universiti Sains Malaysia (USM) community in particular and society in general. The Library realizes that the expertise to manage reading materials shouldn‟t be keep by its own, but rather to be shared to others in need. Since its inception in 2009, various programs have been carried out to meet the objective. Numerous programs were conducted under three main programs, namely Community Network, Exhibition and Sharing is Caring. Starting as small-scale projects, now these initiatives have shown its positive impacts especially in building foundation for lifelong learning among USM community.